Metodologia badań nad strategiami uczenia się - Pawlak, Mirosław (Neofilolog, 2009)
The last thirty years have witnessed considerable advances in empirical investigations into language learning strategies, with researchers identifying and classifying strategic devices, providing insights into factors influencing their use, investigating the relationship between the application of strategies and proficiency, and appraising the contributions of strategies- based instruction. Such developments have been accompanied by attempts to refine the existing research tools and design more effective ways of accessing learner’s mental processes. These efforts have not been entirely successful, which is unfortunate since methodological problems limit the validity and reliability of research findings and preclude comparisons between studies, thus stymieing further development of the field. The article evaluates the most frequently used tools and procedures in research on language learning strategies and offers guidelines on how future studies of this kind should most beneficially be conducted.